Spain - Dependants of Volunteers : memorandum of interview / Mr. Brailsford ; Sir Walter Citrine - Brailsford, Henry Noel, 1873-1958; Citrine, Walter, 1887-1983
1937-02-04 034-0200-001 292/946/34/200(i)